2015
DOI: 10.1021/acs.iecr.5b01511
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Performance of Irregular Microvoids in Electrophoresis Separations

Abstract: Within the last decade, novel gel materials with a modified internal morphology have been synthesized and are available for a wide range of applications including drug delivery, separation of biomolecules with relevance in clinical diagnostics, electrokinetic pumping, and sensors 1-3 . One way to achieve this internal modification is to embed nanoparticles into the polymer matrix, so that when an electrical field is applied to the system, the presence of these particles can change the biomacromolecule transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 25 publications
3
5
0
Order By: Relevance
“…This implies that the effective dispersion decreases as the pore tends to be more strait in their shape. The results are consistent (qualitatively) with those published by Simhadri [14]. This type of results is a clear indication of the dramatic role played by the geometry of the domain on the values of the effective transport coefficients that control the motion of the macromolecules inside the pores of the gel matrix.…”
Section: Parametric Analysis Of the Effective Transport Coefficients And Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This implies that the effective dispersion decreases as the pore tends to be more strait in their shape. The results are consistent (qualitatively) with those published by Simhadri [14]. This type of results is a clear indication of the dramatic role played by the geometry of the domain on the values of the effective transport coefficients that control the motion of the macromolecules inside the pores of the gel matrix.…”
Section: Parametric Analysis Of the Effective Transport Coefficients And Discussionsupporting
confidence: 91%
“…The effects of these geometrical parameters as well as the molecule charges and the magnitude of the applied orthogonal electrical field on the optimal separation time are illustrated. Furthermore, a qualitative agreement between the predictions reported here with those published by Simhadri et al [14] is observed. Both predictions (those communicated here and those by Simhadri et al [14]) are in agreement with experimental evidences reported by Thompson et al [17].…”
supporting
confidence: 91%
See 3 more Smart Citations